Pentingnya Sarapan Sehat Bagi Siswa Sekolah Dasar Di SD Alkhairat Tobelo - Yayu, Putri; Jumriani; Nurbaety; Nur Islamyati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Breakfast is an important part of a healthy diet, especially for elementary school children. Good breakfast habits have been shown to support children's physical, cognitive, and emotional development. Children who eat breakfast regularly tend to have better concentration in learning, more stable energy throughout the day, and higher academic performance compared to children who do not eat breakfast. Several studies have found that children who do not eat breakfast have lower blood glucose levels in the morning, which contributes to decreased short-term memory and problem-solving abilities. In addition, irregular breakfast is also associated with an increased risk of obesity, because children tend to consume foods high in sugar and fat outside of main meal times. This activity aims to increase knowledge and form positive, sustainable habits. This community service was carried out on Thursday, April 21, 2025 at Alkhairaat Elementary School, Tobelo, North Halmahera Regency, using a participatory educational approach method, which actively involves students in the learning process. This activity was attended by 24 children, 1 teacher, 4 lecturers, before being given education most of the children did not know the importance of a healthy breakfast for elementary school children and after being given education 90% of children had good knowledge about the importance of a healthy breakfast for elementary school children.